The Improvement of Ultra-Soft Soil Using Prefabricated Vertical Drain with Vacuum Preloading System: Laboratory Model Study - Pio Kefas; Andreas Erdian Wijaya; Ginanjar Khaq; Marcello Djunaidy (Indonesian Geotechnical Journal, 2023)
Use of Prefabricated Vertical Drain (PVDs) to improve ultra-soft soil by vacuum preloading method on laboratory scale is described in this study. The laboratory model will be carried out in a vacuum chamber 1m x 1m x 1m with 1 (one) PVD in the middle which is connected to the vacuum pump. During vacuum preloading test, 3 (three) units of settlement plates will be monitored until 60 days. As a comparison data on soil conditions, a test will be carried out by taking 2 (two) samples to see the distribution of differences in the properties condition of ultra-soft soil before and after vacuuming and its relationship with the settlement. Laboratory test shown properties changes which the soil nearest PVD has the bigger changes compared to soil farther from PVD. The change in unit weight (g) based on the sample distance of 15cm and 45cm from the PVD was an increase of 16.47% and 9.59%, respectively. While the change in natural water content (wn) was down 92.81% and 34.47% respectively. Meanwhile, the results of the permeability test showed a decrease of 97.05% and 85.77%, respectively.